The quantified worker : law and technology in the modern workplace / Ifeoma Ajunwa, University of North Carolina School of Law. - Ajunwa, Ifeoma (Cambridge University Press, 2023)
The information revolution has ushered in a data-driven reorganization of the workplace. Big data and AI are used to surveil workers and shift risk. Workplace wellness programs appraise our health. Personality job tests calibrate our mental state. The monitoring of social media and surveillance of the workplace measure our social behavior. With rich historical sources and contemporary examples, The Quantified Worker explores how the workforce science of today goes far beyond increasing efficiency and threatens to erase individual personhood. With exhaustive detail, Ifeoma Ajunwa shows how different forms of worker quantification are enabled, facilitated, and driven by technological advances. Timely and eye-opening, The Quantified Worker advocates for changes in the law that will mitigate the ill effects of the modern workplace.